207 Patients'motivations and expectations when seeking urgent care at emergency departments and acceptability of primary care streaming: a realist study. Issue 12 (23rd November 2020) - Edwards, Michelle; Price, Delyth; Hepburn, Julie; Harrington, Barbara; Evans, Bridie; Cooper, Alison; Edwards, Adrian
Abstract : Aims/Objectives/Background: We aim to explain the contexts and mechanisms that influence patients' motivations and expectations when accessing urgent care at an ED and their acceptability of being streamed to a primary care clinician working in or alongside the ED. Recent healthcare policy has encouraged the implementation of primary care services in or alongside emergency departments whereby patients with low acuity illness are streamed to a primary care clinician after a brief initial assessment. Our findings describe patients' motivations, expectations, and acceptability of primary care streaming and their level of satisfaction. Methods/Design: We recruited 24 patients to be interviewed after visiting an emergency department for one of five low acuity complaints. 12 patients were streamed to ED clinicians and 11 were streamed to primary care clinicians. We carried out semi-structured realist style interviews by telephone and carried out a realist analysis to create theories to explain motivations to attend, acceptability of streaming and satisfaction with care. Results/Conclusions: Motivations for attending the ED included patients' perception of their complaint as an emergency which needed immediate treatment, and previous experience of receiving care at the ED. Acceptability of primary care streaming was related to patients' past experiences accessing primary care services, their trust in initial assessment processes and their expectation to be seen by 'expert clinicians' on the 'same day'. When patients' expectations of waiting times, level of investigations and general quality of care were met or exceeded, they reported acceptability to being streamed to a primary care clinician and were satisfied with their care. Understanding why patients attend the ED for urgent care needs and their experience of primary care streaming is essential to addressing increasing ED demand and improving efficiency.